Dural ectasia of the optic nerve sheath: is it always benign? - Berker Bakbak; Hava Dönmez; Tülay Kansu; et al (Eye and Brain, 2009)
Berker Bakbak1, Hava Dönmez2, Tülay Kansu3, Hayyam Kiratli41Hacettepe University Institute of Neurological Sciences and Psychiatry, Neuro-ophthalmology Unit, Ankara, Turkey; 2Diskapi Yildirim Beyazid Education and Research Hospital Neurology Clinic, Ankara, Turkey; 3Hacettepe University Medical Faculty, Department of Neurology, Neuro-Ophthalmology Unit, Ankara, Turkey; 4Hacettepe University Medical Faculty, Department of Ophthalmology, Ocular Oncology Unit, Ankara, TurkeyAbstract: A 36-year-old woman with a 3-month history of progressive visual loss had papilledema, dilatation of the optic nerve sheaths and normal cerebrospinal fluid pressures. She was diagnosed as dural ectasia of the optic nerve sheaths and surgical decompression was performed. In this case report, severe visual loss is described as a serious complication of this rare disease and the importance of early surgical intervention is emphasized.Keywords: optic nerve, dural ectasia, meningocele